Integrasi Ekoteologi dan Prinsip Intelektualitas, Spiritualitas, Integritas (ISI) dalam Penguatan Manajemen Pendidikan Islam Berbasis Nilai - M. Aditiya Imansyah; Juanda; Deti Elice; Chairul Amriyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This research is motivated by the increasingly urgent need to integrate ecotheological values ​​into Islamic Education Management (MPI) as a response to the global ecological crisis and environmental moral degradation in educational institutions. The purpose of this research is to analyze how ecotheological values ​​can be internalized in madrasah policies, curricula, and managerial practices, and to develop a conceptual model for managing ecologically-minded Islamic education. The main problem examined is the weak translation of the spiritual values ​​of khalīfah and amanah into a concrete managerial system. This research uses a contextual qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation review at MTs Al-Hidayah Sukajaya, Bandar Lampung. The results show that the successful integration of ecotheology into MPI depends on the synergy of three main aspects: ontology (spiritual values), epistemology (sources of Islamic and environmental knowledge), and axiology (managerial goals). It was also found that the desire for an ecologically-minded education program requires the support of madrasah policies, teacher capacity building, and partnerships with environmental institutions.